Successful amplification of DNA aboard the International Space Station. (December 2017) - Boguraev, Anna-Sophia; Christensen, Holly; Bonneau, Ashley; Pezza, John; Nichols, Nicole; Giraldez, Antonio; Gray, Michelle; Wagner, Brandon; Aken, Jordan; Foley, Kevin; Copeland, D.; Kraves, Sebastian; et al.
Abstract As the range and duration of human ventures into space increase, it becomes imperative that we understand the effects of the cosmic environment on astronaut health. Molecular technologies now widely used in research and medicine will need to become available in space to ensure appropriate care of astronauts. The polymerase chain reaction (PCR) is the gold standard for DNA analysis, yet its potential for use on-orbit remains under-explored. We describe DNA amplification aboard the International Space Station (ISS) through the use of a miniaturized miniPCR system. Target sequences in plasmid, zebrafish genomic DNA, and bisulfite-treated DNA were successfully amplified under a variety of conditions. Methylation-specific primers differentially amplified bisulfite-treated samples as would be expected under standard laboratory conditions. Our findings establish proof of concept for targeted detection of DNA sequences during spaceflight and lay a foundation for future uses ranging from environmental monitoring to on-orbit diagnostics.